A study of the role of multiple layer‐by‐layer assembled bionic extracellular matrix in promoting wound healing via activation of the Wnt signaling pathway. Issue 6 (12th January 2023) - Wang, Zehui; Cao, Kun; Yan, Di; Ge, Yangjing; Li, Ruiyuan; Liu, Yanwen; Ma, Ting; Sun, Xiaojuan
Abstract: Wound healing is a multicellular collaborative process in which the adhesion and proliferation of fibroblasts in the wound is the basis for ensuring rapid wound healing, and in this process, it can promote the regeneration and remodeling of tissue and extracellular matrix. Studies have shown that Arg‐Gly‐Asp adhesive peptide (RGD) and basic fibroblast growth factor (bFGF) can stimulate the adhesion and proliferation of fibroblasts by activating the Wnt/β‐catenin signaling pathway, respectively. This study adopts the principle of layer‐by‐layer self‐assembly, and the binding force formed by electrostatic attraction and Schiff base was used to combine bFGF and RGD with collagen membrane to form a biomimetic membrane that is non‐cytotoxic with strong biocompatibility that could promote soft tissue healing. The surface characteristics of MLCM and the sustained release concentration of bFGF in vitro were measured, and the effects of MLCM on cell viability, proliferation, migration, and wound healing by means of Wnt/catenin pathways were studied through cell experiments and animal experiments under the comparison of negative control groups and positive control groups. The results showed that MLCM could stimulate wound healing more actively and had a positive effect on cell activity, proliferation, and migration. During wound healing, MLCM activates the Wnt/β‐catenin signaling pathway and inhibition of Wnt/β‐catenin signaling pathway significantly reduces the positive effects of MLCM on wound healing.